Production and quality of hydroponic corn fodder cultivated in various substrates and harvested at different times - Luz, Geovani Gabriel Gonçalves da; Codognoto, Luciane da Cunha; Ribeiro, Alessandra de Jesus; Conde, Thassiane Telles; Sousa, Magda Lucia Pereira de; Poletto, Amanda de Oliveira (Acta Scientiarum. Animal Sciences, 2025)
In the adaptation of the hydroponic cultivation technique, fodder species can be obtained from germination to seedling cultivation, to obtain fresh green food of superior quality, to supplement animal feed. Thus, this experiment aimed to evaluate productive and qualitative aspects of hydroponic corn fodder produced on different organic substrates (rice husk, coffee husk, sugarcane bagasse, and corn straw) in two cultivation periods (up to the 10 and 15th days after sowing). This was a 5 x 2 factorial completely randomized experimental design, with four replications, totaling 40 experimental plots. Sugarcane bagasse and coffee husk did not promote the aerial development of corn seedlings in hydroponic fodder cultivation, considering that they were green materials and had not been subjected to prior composting. The substrates tested showed significantly higher substrate dry biomass and total dry matter (DM) production than the control hydroponic fodder (no substrate). Cultivation of hydroponic corn fodder up to the 10th day after sowing resulted in higher total DM production. Hydroponic fodder obtained from rice husk showed higher DM, neutral detergent fiber, and acid detergent fiber contents, for harvesting after 15 days of cultivation, differing significantly from the control treatment. Hydroponic fodder from coffee husk substrate had higher lignin and ash contents, showing lower nutritional quality of the food.